0653 Positive Effects of Long Term Continuous Positive Airway Pressure Therapy on Blood Pressure in Obstructive Sleep Apnea Patients. (27th May 2020) - Shirahama, R; Tanigawa, T; Tomooka, K; Fan Yun, L; Ikeda, A; Wada, H; Kales, S N
Abstract: Introduction: Obstructive sleep apnea (OSA) is one of the common causes of hypertension. Therefore, we examine the longitudinal effect of continuous positive airway pressure (CPAP) therapy and its adherence on blood pressure among OSA patients. Methods: One thousand two hundred ninety-three (male 1, 130, female 163) patients, who were diagnosed with OSA and underwent CPAP therapy were investigated for longitudinal changes (24 months observation period) in the levels of blood pressure and body weight. The longitudinal analyses were performed by mixed effect model. Multiple Imputation with Chained Equations was also used to impute missing data. Good CPAP adherence is defined as more than 70% of the time using CPAP more than 4hours at all the measuring. Poor CPAP adherence is defined as less than 70% of the time using CPAP more than 4hours at all the measuring time points. Results: The patient group with good CPAP adherences), compared to poor CPAP adherence, showed significant diastolic blood pressure reduction in 24 months follow-up period (β=-0.13, p=0.03) despite a lack of significant weight loss (β=-0.02, p=0.59). However, no significant associations were found between systolic blood pressure and CPAP adherence (β=-0.14, p=0.11). Conclusion: CPAP therapy was found to have a longitudinal effect on diastolic blood pressure despite a lack of significant weight loss. Support: